2016
DOI: 10.1210/en.2016-1257
|View full text |Cite
|
Sign up to set email alerts
|

The NADPH Oxidase Nox2 Mediates Vitamin D-Induced Vascular Regeneration in Male Mice

Abstract: 1α,25-dihydroxy-vitamin D3 (1,25D) exerts protective effects in the vascular system and promotes myeloid cell differentiation, which are important sources of reactive oxygen species. Given that myeloid cell reactive oxygen species derives from Nox-family NADPH oxidases, we hypothesized that this enzyme family contributes to the beneficial effects of 1,25D on vascular regeneration. The function of Nox enzymes in this context was studied in the murine carotid artery electric injury regeneration model. Male mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Wound-induced release of ROS has been shown to be a key regulator of wound healing and regeneration ( Leisegang et al, 2016 ; Serras, 2016 ; Yoo et al, 2012 ). Our earlier work demonstrated that early ROS signaling immediately before and after damage, mediated fin regeneration three days later ( Yoo et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Wound-induced release of ROS has been shown to be a key regulator of wound healing and regeneration ( Leisegang et al, 2016 ; Serras, 2016 ; Yoo et al, 2012 ). Our earlier work demonstrated that early ROS signaling immediately before and after damage, mediated fin regeneration three days later ( Yoo et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, VD modulates the vascular effects of AGEs by reducing the diabetes-induced increase of IL-6 and of NFκB-p65 DNA binding activity, both key mediators of AGEs signalling [135]. AGEs and RAGE are among the major pathways involved in the pathophysiology of diabetic complications and of DR [136], as their interaction induces the translocation of NF-κB, and the subsequent transcription of endothelial dysfunction biomarkers, such as intercellular adhesion molecule-1 (ICAM-1), endothelin-1, and E-selectin [137].…”
Section: Vd Modulates Inflammation and The Immune Systemmentioning
confidence: 99%